Derechos humanos: sexuales y reproductivos en Senguio, Michoacán - Sandoval Velázquez, Elizabeth (Universidad Michoacana de San Nicolás de Hidalgo, 2012)
The National Human Rights Commission (CNDH) of Mexico defines human rights as the set of prerogatives inherent in the nature of the person, whose effective realization is indispensable for the integral development of the individual living in a legally organized society 1. Human rights arise from the reproductive rights that underpin social structures such as "free motherhood and responsible parenthood" 2, as well as designate a set of human rights related to reproductive health; As well as civil, political, social, cultural, economic, family and legal rights, from which the right to health, the right to marriage, a family, freedom, integrity, security, Discrimination, privacy and privacy, which are so important for the development of the human being, especially women.

La Comisión Nacional de los Derechos Humanos (CNDH) de México define a los derechos humanos como el conjunto de prerrogativas inherentes a la naturaleza de la persona, cuya realización efectiva resulta indispensable para el desarrollo integral del individuo que vive en una sociedad jurídicamente organizada 1 . De los derechos humanos surgen los derechos reproductivos que fundamentan estructuras sociales como “la maternidad libre y la paternidad responsable” 2 , además de designar un conjunto de derechos humanos relacionados con la salud reproductiva; así como derechos civiles, políticos, sociales, culturales, económicos, familiares y jurídicos, de los que se desprenden el derecho a la salud, el derecho al matrimonio, a una familia, a la libertad, la integridad, la seguridad, a la no discriminación, a la privacidad y a la intimidad, y que son tan importantes para el desarrollo del ser humano, en especial a las mujeres.
Facultad de Derecho y Ciencias Sociales. Maestría en Derecho
Keywords: info:eu-repo/classification/cti/5; FDCS-M-2012-0528; Procesal constitucional; Sexual; Reproductivos; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/501